Keeping Cool : Embedding Resilience in the Initial Teacher Education Curriculum : Final Report. - Mansfield, Caroline; Price, Anne; McConney, Andrew; Beltman, Susan; Pelliccione, Lina; Wosnitza, Marold (Office for Learning and Teaching, 2012)
There is an alarming rate of attrition among early career teachers, both in Australia and internationally, with 25-40 per cent of early career teachers leaving the profession in their first five years. Investigations of teacher attrition have largely focused on stress and burnout. However, more recent perspectives have considered how teacher resiliency influences retention. This is the final report from a project that drew on the experiences of early career teachers and pre-service teacher education students to identify key characteristics of resilient teachers, and gain a deeper understanding of how, and in what contexts, resilience develops. These understandings will form the basis of an effective practice framework for the redesign of the teacher education curriculum. Key deliverables of the project include development of a resiliency framework for initial teacher education, development of an instrument to measure constructs associated with teacher resiliency, and an interactive website to promote resiliency among pre-service teachers and early career teachers.